Optimal Parameters of Laser Therapy to Improve Critical Calvarial Defects - Santos, Matheus AFM; Silva, Daniela N.; Rovaris, Karla; Sousa, Frederico B.; Dantas, Eugenia LA; Loureiro, Lucas A.; Pereira, Thiago M. C.; Meyrelles, Silvana S.; Bertollo, Rossiene M.; Vasquez, Elisardo C. (Frontiers in Physiology, 2022)
Body bones play diverse pivotal roles, including the protection of vital organs. For instance, the integrative functions of the brain controlling diverse peripheral actions can be affected by a traumatic injury on the calvaria and the reparative process of a large defect is a challenge in the integrative physiology. Therefore, the development of biomaterials and approaches to improve such defects still requires substantial advances. In this regard, the most attractive approaches have been covering the cavity with inorganic bovine bone (IBB) and, more recently, also using low-level laser therapy (LT), but this issue has opened many questions. Here, it was determined the number of LT sessions required to speed up and to intensify the recovery process of two 5-mm-diameter defects promoted in the calvaria of each subgroup of six adult Wistar rats. The quantitative data showed that 30 days post-surgery, the recovery process by using blood clot-filling was not significantly influenced by the number of LT sessions. However, in the IBB-filled defects, the number of LT sessions markedly contributed to the improvement of the reparative process. Compared to the Control group (non-irradiated), the percentage of mineralization (formation of new bone into the cavities) gradually increased 25, 49, and 52% with, respectively, 4, 7, and 11 sessions of LT. In summary, combining the use of IBB with seven sessions of LT seems to be an optimal approach to greatly improve the recovery of calvarial defects. This translational research opens new avenues targeting better conditions of life for those suffering from large bone traumas and in the present field could contribute to preserve the integrative functions of the brain.